Response to direct and indirect recruitment for a randomised dental clinical trial in a multicultural population of elders - MacEntee MI, Wyatt C, Kiyak HA, Hujoel PP, Persson RE, Persson GR, Powell LV. (Blackwell Synergy, 2002)
Recruitment for randomised clinical trials and community-based studies has received little attention in the dental literature. The goal of this study was to report on our experiences with direct and indirect recruitment methods for a trial to prevent tooth loss in elders.